Livelihood Diversity Strategies of Rural Women in Imo State, Nigeria - E C Matthews-Njoku; O M Adesope (Journal of Agricultural Extension, 2007)
The objectives of this study include describing the socio- economic characteristics of the respondents' in the study area, to identify the livelihood diversity strategies of respondents to determine the impact of livelihood diversity strategies on respondents, to determine the relationship between socio- economic characteristics of respondents and their livelihood diversity strategies. Data were collected with the aid of structured questionnaire and interview schedule from 132 randomly selected respondents. Data collected were analyzed using frequency percentage and mean and chi square. The findings of the study revealed that rural women in theÂ  study area indicated that they were involved in the following important livelihood diversity strategies: Petty trading, Thrift savings. Farming. Cooking at occasions, and Hair plaiting. The major impact of the livelihood strategies identified include ability to feed adequately, ability to buyland for farming, buying more farm inputs, paying rent, proper children education, and improved health care. Findings showed that educational level(X = 38.323, p<0.05), household size (X = 41.250. p<0.05) and income (X2 = 62.857, p<0.05) significantly influenced livelihood diversity strategies of respondents. It was recommended that enabling environment should be created for women to participate in more livelihood diversity strategies to furtheraidinpovertyalleviation.